Language as a Tool for Care: Unraveling the Directive Speech Acts in Nursing Communication - Daar, Gabriel Fredi; Jemadi, Fransiskus; Gunas, Tobias (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This study aims to explore types of directive speech acts used in nurse-patient communication and understand why particular speech acts are used within this context. The research was carried out at Nursing Department, Universitas Katolik Indonesian Santu Paulus Ruteng, Flores. The study involved 20 participants, 18 nursing students with hospital internship experience and two nursing lecturers. Data were collected through interviews, focus group discussions (FGDs), and documents, then analysed using the interactive model by Miles et al. (2014). The results show that requesting speech acts are typically delivered in indirect and polite forms to maintain respect and patient autonomy. Recommending and advising speech acts are employed to encourage patients and families to make informed decisions regarding treatment and health behavior. These speech acts are crucial in fostering cooperation without imposing authority. It aligns with the principles of patient-centered care. Meanwhile, directing speech acts are used for both clinical instructions and logistical guidance within the hospital. It aims to show clarity and precision as an essential aspect for safety and efficiency. The study highlights that nurses tend to avoid direct commanding speech acts, opting instead for more polite and empathetic expressions. This approach supports the psychological comfort of patients while achieving effective communication. The appropriate and polite use of directive speech acts is essential in achieving successful health outcomes and enhancing the quality of nursing communication.